Dampak Pemanfaatan Handphone atau Gawai Terhadap Minat Membaca Murid SMAS Bhaktyarsa - Rani, Maulani Meutia; Syam, Salmaini Safitri; Firdaus, Aditya; Refiona Andika (Global Action and Education for Society, 2025)
Mathematical communication is one of the skills of students who can describe the ability to understand concepts, express ideas through mathematical symbols, interpret and represent mathematics in their language. However, these skills are poorly trained in the classroom. The purpose of this study is to describe students' mathematical communication skills after applying the Realistic Mathematics Education (RME) model. The research method used is qualitative descriptive by describing written answers and interviews on students' mathematical communication skills. The subjects of the study were 28 grade 5 students at a school in Bukittinggi, West Sumatra. After the implementation of the RME, students' mathematical communication skills in the aspect of problem comprehension increased by 37,1 points, the aspect of strategic ability increased by 23,32 points and the ability of interesting conclusions increased by 29,28 points. The use of the RME learning model in the classroom provides opportunities for students to collaborate with their colleagues in solving real-world context problems. Therefore, the application of RME in the classroom can improve students' mathematical communication skills in elementary school which involves aspects of understanding problems and strategic skills in the use of mathematical symbols and providing conclusions to solve problems that have been carried out.